MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMK N 1 KOTA JAMBI - SUSANTI, ZUYUN SITI NURFINA; MUNANDAR, ARIS; EFFENDI, WAHYU AGUNG; PUTRI, AMELIA; LESTARI, RISKA DWI; DIANTIKA, DWI NUR; ROPITA, ROPITA; SYAH, MUHAMMAD AIDIL; ZULIANA, RIZQI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
The school principal is one of the key components in education that significantly influences the improvement of teacher performance. The success of a school’s education is largely determined by the principal’s ability to manage the educational staff available at the school. This study aims to reveal the leadership of the school principal in improving teacher performance in conducting teaching and learning activities at SMK Negeri 1 Kota Jambi. The research focuses on the principal's management in enhancing teacher performance at SMK Negeri 1 Kota Jambi. The aspects highlighted in this study include discipline, responsibility, pride in the profession, and the hard work of the principal at SMK Negeri 1 Kota Jambi. The objective of this research is to understand the principal’s management in improving teacher performance at SMK Negeri 1 Kota Jambi.The type of research used is descriptive qualitative, a research method that produces descriptive data in the form of words, both written and oral, from observed individuals, using a holistic approach that does not separate individuals or organizations into separate variables but views them as part of a whole system. Data collection techniques in this study include interviews, observations, and documentation. Data analysis is conducted using qualitative analysis methods. The results of the study show that after receiving guidance and direction from the Principal of SMK Negeri 1 Kota Jambi, teachers' abilities have significantly improved compared to before. ABSTRAKKepala sekolah merupakan salah satu komponen pendidikan yang paling berpengaruh dalam meningkatkan kinerja guru adalah kepala sekolah. Keberhasilan pendidikan sekolah sangat bergantung pada seberapa baik kepala sekolah mengelola tenaga kependidkan. Penelitian ini meneliti manajemen kepala sekolah untuk meningkatkan kinerja guru di SMK Negeri 1 Kota Jambi. Penelitian ini berfokus pada kedisiplinan, tanggung jawab, rasa bangga terhadap profesi, dan kerja keras kepala sekolah.Tujuan penelitian ini adalah untuk mendapatkan pemahaman yang lebih baik tentang peran manajemen kepala sekolah dalam meningkatkan kinerja guru di SMK Negeri 1 Kota Jambi. Penelitian deskriptif kualitatif adalah jenis penelitian yang menghasilkan data deskriptif berupa kata-kata dari orang-orang yang diamati, baik secara tertulis maupun lisan. Pendekatan holistik melihat individu atau organisasi sebagai komponen dari suatu kesatuan, bukan sebagai variabel terpisah. Dalam penelitian ini, data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Metode analisis kualitatif digunakan untuk menganalisis data. Hasil penelitian menunjukkan bahwa kemampuan guru SMK Negeri 1 Kota Jambi meningkat secara signifikan setelah mendapat bimbingan dan arahan dari kepala sekolah.